Etablierung einer Injektionsnarkose mit Ketamin und Medetomidin für die Fossa (Cryptoprocta ferox) - Langer, Sandra; Justus Liebig University Giessen (My University, 2014)
In dieser Studie wurde erstmals ein modernes, tierart- und tierschutzgerechtes Anästhesieverfahren für Madagaskars größtes Raubtier, die Fossa (Cryptoprocta ferox), untersucht. Dafür wurden 19 Fossas, davon 13 männliche und 6 weibliche, in vier deutschen zoologischen Einrichtungen und einer Privathaltung mit einer Kombinationsanästhesie aus Medetomidin und Ketamin narkotisiert. Die Untersuchungen wurden unter weitestgehend standardisierten Bedingungen und unter Berücksichtigung möglicher geschlechts- und altersspezifischer Unterschiede durchgeführt.

Establishment of an anesthesia protocol for the fossa (Cryptoprocta ferox) with the use of ketamine and medetomidine With this study a modern species-specific anesthesia protocol was developed for the first time for Madagascar´s largest extant carnivore the fossa (Cryptoprocta ferox). 19 fossas, of which 13 males and 6 females, living at four zoological gardens and with one private holder in Germany were anesthetized with the combination of medetomidine and ketamine. The experiment was carried out under predominantly standardized conditions and possible sex- and age-related differences were taken under consideration.
Keywords: ddc:630